Association of epicardial adipose tissue with proteomics, coronary flow reserve, cardiac structure and function, and quality of life in heart failure with preserved ejection fraction: insights from the PROMIS-HFpEF study - Venkateshvaran Ashwin; Faxen Ulrika Ljung; Hage Camilla; Michaelsson Erik; Svedlund Sara; Saraste Antti; Beussink-Nelson Lauren; Fermer Maria Lagerstrom; Gan Li-Min; Tromp Jasper; Lam Carolyn SP; Shah Sanjiv J; et al. (Wiley, 2022)
Aim: Epicardial adipose tissue (EAT) may play a role in the pathophysiology of heart failure with preserved ejection fraction (HFpEF). We investigated associations of EAT with proteomics, coronary flow reserve (CFR), cardiac structure and function, and quality of life (QoL) in the prospective multinational PROMIS-HFpEF cohort.
Methods and results: Epicardial adipose tissue was measured by echocardiography in 182 patients and defined as increased if ≥9 mm. Proteins were measured using high-throughput proximity extension assays. Microvascular dysfunction was evaluated with Doppler-based CFR, cardiac structural and functional indices with echocardiography and QoL by Kansas City Cardiomyopathy Questionnaire (KCCQ). Patients with increased EAT (n = 54; 30%) had higher body mass index (32 [28-40] vs. 27 [23-30] kg/m2 ; p < 0.001), lower N-terminal pro-B-type natriuretic peptide (466 [193-1133] vs. 1120 [494-1990] pg/ml; p < 0.001), smaller indexed left ventricular (LV) end-diastolic and left atrial (LA) volumes and tendency to lower KCCQ score. Non-indexed LV/LA volumes did not differ between groups. When adjusted for body mass index, EAT remained associated with LV septal wall thickness (coefficient 1.02, 95% confidence interval [CI] 1.00-1.04; p = 0.018) and mitral E wave deceleration time (coefficient 1.03, 95% CI 1.01-1.05; p = 0.005). Increased EAT was associated with proteomic markers of adipose biology and inflammation, insulin resistance, endothelial dysfunction, and dyslipidaemia but not significantly with CFR.
Conclusion: Increased EAT was associated with cardiac structural alterations and proteins expressing adiposity, inflammation, lower insulin sensitivity and endothelial dysfunction related to HFpEF pathology, probably driven by general obesity. Potential local mechanical or paracrine effects mediated by EAT remain to be elucidated.